My man Godfrey [videorecording (DVD)] - Powell, William, 1892-1984; Lombard, Carole, 1908-1942; Pallette, Eugene, 1889-1954; Dixon, Jean, 1896-1981; Patrick, Gail, 1911-1980; Mowbray, Alan, 1896-1969; Brady, Alice, 1892-1939; La Cava, Gregory, 1892-1952; Hatch, Eric, 1901-1973 (Legend Films, 2008)
A scatterbrained socialite hires a vagrant as a family butler ... but there's more to Godfrey than meets the eye.